One size fits none - a qualitative study investigating nine national quality registries' conditions for use in quality improvement, research and interaction with patients - Vibeke Sparring; Emma Granström; Magna Andreen Sachs; Mats Brommels; Monica E. Nyström (BMC, 2018)
Abstract Background Swedish National Quality Registries (NQRs) are observational clinical registries that have long been seen as an underused resource for research and quality improvement (QI) in health care. In recent years, NQRs have also been recognised as an area where patients can be involved, contributing with self-reported experiences and estimations of health effects. This study aimed to investigate what the registry management perceived as barriers and facilitators for the use of NQRs in QI, research, and interaction with patients, and main activities undertaken to enhance their use for these purposes. The aim was further to identify potential differences between various types of NQRs for their use in these areas. Methods In this multiple case study, nine NQRs were purposively selected. Interviews (n = 18) were conducted and analysed iteratively using conventional and directed content analysis. Results A recent national investment initiative enabled more intensive work with development areas previously identified by the NQR management teams. The recent focus on value-based health care and other contemporary national healthcare investments aiming at QI and public benchmarking were perceived as facilitating factors. Having to perform double registrations due to shortcomings in digital systems was perceived as a barrier, as was the lack of authority on behalf of the registry management to request participation in NQRs and QI activities based on registry outcomes. The registry management teams used three strategies to enhance the use of NQRs: ensuring registering of correct and complete data, ensuring updated and understandable information available for patients, clinicians, researchers and others stakeholders, and intensifying cooperation with them. Varied characteristics of the NQRs influenced their use, and the possibility to reach various end-users was connected to the focus area and context of the NQRs. Conclusions The recent national investment initiative contributed to already ongoing work to strengthen the use of NQRs. To further increase the use, the demands of stakeholders and end-users must be in focus, but also an understanding of the NQRs' various characteristics and challenges. The end-users may have in common a need for training in the methodology of registry based research and benchmarking, and how to be more patient-centred.